A case report of ganglion cell complex change in incipient nonarteritic anterior ischemic optic neuropathy. Issue 6 (November 2020) - Kim, Jiyeon; Gupta, Arvind
Background: Incipient nonarteritic anterior ischemic optic neuropathy is a heavily underdiagnosed ophthalmic condition due to its nature of being asymptomatic. Only a handful of cases have been reported and, therefore, limited information is available in respect to it. To date, incipient nonarteritic anterior ischemic optic neuropathy has been viewed as threatened nonarteritic anterior ischemic optic neuropathy, which does not cause any symptoms or structural change to the affected eye. Case presentation: A 68-year-old female was diagnosed with right incipient nonarteritic anterior ischemic optic neuropathy and left classic nonarteritic anterior ischemic optic neuropathy. Despite her right eye remaining asymptomatic, the optical coherence tomography scan of her right macula at her 3-month follow-up appointment showed thinning of retinal nerve fibre layer and ganglion cell complex. Conclusions: To our knowledge, this is the first ever case report describing a thinning of ganglion cell complex in a patient with incipient nonarteritic anterior ischemic optic neuropathy. This suggests that contrary to current belief, incipient nonarteritic anterior ischemic optic neuropathy can result in subclinical structural changes to the affected eye.